Antarctic Bioprospection: Marching Towards a sui Generis Legal Institutionality? - Villamizar Lamus, Fernando (Vniversitas, 2015)
Antarctic bioprospection is an activity that becomes more and more important with each passing day due to its geopolitical implications. Also, because should it be successful, it could generate massive profits for those performing it. In this context, the purpose of this article is to make a review of how the legal regulation of the Antarctic bioprospection has been performed and also about the beginning of a certain emerging institutionality for its regulation. The methodology used is based on a document review of the main academic proposals and the documents of the Antarctic Treaty System (ATS), as well as of the databases that record the antarctic bioprospection activities. From the review performed we conclude that certain proposals to regulate Antarctic bioprospection have been accepted in some measure and have been implemented by entities related to the ATS, but not fully part of it, which creates a sui generis institutionality. This implies that the ATS as such still has to fully address the issues related to this topic. La bioprospección en la Antártida es una actividad que día a día toma mayor importancia, por sus implicaciones geopolíticas y porque, de ser exitosa, puede generar sumas millonarias en utilidades para quienes la realicen. En ese contexto, el objetivo del presente artículo es hacer una revisión de cómo se ha abordado la regulación jurídica de la bioprospección antártica y de cómo se ha empezado a generar de manera incipiente cierta institucionalidad para su regulación. La metodología empleada se basa en una revisión documental de las principales propuestas académicas y documentos del Sistema del Tratado Antártico, STA, y de las bases de datos que registran las actividades de bioprospección antártica. De la revisión realizada, se puede concluir que ciertas propuestas para regular la bioprospección antártica han sido acogidas en alguna medida e implementadas por entes relacionados con el STA pero no propios de este, lo cual genera una institucionalidad reguladora sui géneris. Esto implica entonces que el STA como tal está en mora de abordar integralmente toda la problemática alrededor de este tema.